Post-traumatic lip lesion mimicking rhabdomyomatous mesenchymal hamartoma in a pediatric patient - Jiménez Polanco, Xiomara Beatriz; Torres, Carolina Paes; Silveira, Heitor Albergoni [UNESP]; Almeida, Luciana Yamamoto [UNESP]; Bezerra Segato, Raquel Assed; León, Jorge Esquiche (My University, 2020)
We report a 7-year-old boy who presented with a nodule on the upper lip. A previous clinical history of mechanical trauma in the lesional area had been noted. After surgical excision, microscopy revealed fibrocollagenous fascicles associated with neurovascular bundles and skeletal striated muscle fibers in diffuse subepithelial distribution, suggesting rhabdomyomatous mesenchymal hamartoma. However, strict clinicopathological correlation favored a healing process with trapped striated skeletal muscle tissue. After three years of follow-up, an improvement in the aesthetic appearance of the upper lip was observed. To the best of our knowledge, a case of pseudo-rhabdomyomatous mesenchymal hamartoma has not been reported to date.
Keywords: Hamartoma; Immunohistochemistry; Lip; Oral diagnosis; Pediatric dentistry